Ketepatan Putusan Bebas No. 36/Pid.Sus/2023/PN Lbb dalam Perkara Tindak Pidana Incest - Harahap, Rizky Olivia Kartina; Sitepu, Rajin (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to determine whether the Acquittal Verdict No. 36/Pid.Sus/2023/PN Lbb in the Incest Crime Case is appropriate or not. The method used is normative juridical. Data was obtained by reviewing library materials such as books, journals, and references related to the Lubuk Basung District Court Verdict No. 36/Pid.Sus/2023/PN Lbb. The results of the study on Verdict 36/Pid.Sus/2023/PN Lbb, the defendant was charged with committing the crime of incest according to